Sistem Rekomendasi Pencarian Buku Perpustakaan Dengan Algoritma Content Based Filtering - Ndaru Hendrayana; Jati Sasongko Wibowo (Elkom: Jurnal Elektronika dan Komputer, 2024)
Well-organized and methodical libraries can, either directly or indirectly, facilitate the teaching and learning process in the community in which they are housed. Manual searching takes a long time because libraries typically have a large number of reading books. Without a book search system, libraries will make it harder and take longer for patrons to find books since they will have to look through each book individually on the shelf. It is quite feasible to create an information retrieval system for libraries to make book searches easier. Based on the parameters or keywords entered, the content-based filtering approach of the library book search information retrieval system can present ten recommendations. The Complete Guide to Islam in Kafah has the highest similarity of 0.775 when it comes to the process of looking for books with religious categories and keywords related to Islam.